If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23x + 23 = 34 Reorder the terms: 23 + 23x = 34 Solving 23 + 23x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + 23x = 34 + -23 Combine like terms: 23 + -23 = 0 0 + 23x = 34 + -23 23x = 34 + -23 Combine like terms: 34 + -23 = 11 23x = 11 Divide each side by '23'. x = 0.4782608696 Simplifying x = 0.4782608696
| 3(3x-1)-3(2x)=1 | | 3n+35= | | 0.9x-2.1-0.9=0.2(5-x) | | 0.029x+2=0.034x | | 7(y-6)+3y=10(y+1) | | 11+18=x+19 | | (2/9)g=8 | | 9(4x+1)=10(3x+2) | | 0.029x+2x=0.034x | | 2849=37(p+20) | | f(x)=2t-3whatisf(7) | | -3x+5=-2(3x+5) | | 15+(-5x)=15-5x | | 3y+4=-1y+-4 | | -7u+11=-9(u-1) | | 0.029+2x=0.034x | | 2x(2x-5)(5x+2)=0 | | 8(-9p+2)-7p= | | 814=-22a | | -2(x-7)=-4x+20 | | 5v-89=2v+34 | | 3n+35=7n+35 | | 9w-10=2(w+9) | | 5+x^2=65 | | -2x+5=20-x | | 3x(x+2)=3x^2+4x-3+2x | | -3(5y-2)-y=-2(y-2) | | 23=3u+8 | | 8x-3.4=3x-6.7 | | -8d-d+7d=72 | | (w-4/-9)(-2/-3) | | -5(y-3)=-15 |